Mechanism and Control of Water–Rock Coupling-Induced Disaster when Mining below the Unconsolidated Confined Aquifer - Zhihua Li; Ke Yang; Xinzhu Hua; Cheng Liu; Peng Zhou; Shengwen Ge (Geofluids)
Theoretical analysis and numerical simulation were conducted to study the disaster-causing mechanism of structural instability of the overlying strata induced by water–rock coupling and effectively prevent and control the powered support jammed accident during mining below the unconsolidated confined aquifer. The influencing factors on the stability of the overlying strata structure were analyzed, and the numerical simulation method of unconsolidated confined aquifer was designed. The disaster-causing mechanism and the evolution process of the stress–displacement–crack field of the overlying strata induced by water–rock coupling were discovered. Meanwhile, the prevention measures for the structural instability of the overlying strata were proposed and verified in some engineering practice. Results show that the stability of the overlying strata structure reduces with the increase in hydraulic pressure, the breaking interval of the main roof, and the decrease in the overlying strata strength and waterproof coal pillar height. The overlying strata structure keeps a stable equilibrium state before the fracture planes through a whole waterproof coal–rock pillar. When the hydraulic pressure is small or the bedrock surface is a thick topsoil layer, the sliding block is in a state of limit equilibrium for the decrease of pressure on the sliding block while the fracture planes through a whole waterproof coal–rock pillar because of the action of unloading during an overlying strata movement. When the hydraulic pressure is high, the pressure on the sliding block remains constant at about hydraulic pressure, and the intact shear fall of the sliding block occurs as a result of the hydraulic pressure of the confined aquifer and the weight of the sliding block, which may result in a powered support jammed accident. However, this type of accident can be prevented by drainage for decreasing hydraulic pressure, presplitting blasting of the hard main roof, overlying strata grouting reinforcement, and increasing the height of the waterproof coal–rock pillar.